Agriculture Category Advantages and Economic Structures in The Region of West Nusa Tenggara Province - Muhamad Hirzan Hadi Muslim; Jamhari Jamhari; Dwidjono Hadi Darwanto (Agro Ekonomi, 2017)
This research aims to identify [1] the highest agricultural category contribution in the West Nusa Tenggara province; [2] basic or non-basic category in current and future; [3] economic structure changes in the agricultural category; [4] classifying agricultural category. This research by a descriptive method. The data analysis by Location Quotient, Dynamic Location Quotient, Shift-Share and Klassen Typology. The results with the highest contribution to the West Nusa Tenggara GRDP is the agriculture category of 23.5%. The highest contribution of an agricultural category to the agricultural category GRDP in West Nusa Tenggara is a Bima Regency of 46.8%. Based on LQ analysis, forestry and logging categories by 2.41% and fisheries category by 1.16% are categorized as a base, and the agriculture category* (agriculture, farming, hunting and agricultural services) is non-base categories of 0.96%. Based on the DLQ analysis, there is a repositioning structure in agriculture category* that Originally non-base 0.96% to a base 1.00%, as for forestry and logging categories and fishery categories remain base. Based on the shift-share analysis, all categories are positive values, the highest category is agriculture category* 1,528,544,064,778.96 (million) influenced by provincial economic growth, industry mix and the influence of competitive advantage. Based on the Klassen Typology analysis, there are two classifications of agriculture category that is the prime classifi cation (forestry and logging category and fishery category) and potential classifi cation (agriculture category*).